2020
DOI: 10.1039/d0cp01099e
|View full text |Cite
|
Sign up to set email alerts
|

Orientation independent vibrational dynamics of lipid-bound interfacial water

Abstract: Vibrational dynamics of water bound to zwitterionic phospholipids is orientation independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…This observation underlines the aforementioned asymmetry of water in response to positively and negatively charged surfaces. Interestingly, water dynamics in contact with zwitterionic lipids do not seem to be affected by the inversion of phosphate and choline (P-C versus C-P) in the headgroup 184 . The effect of the surface charge has also been observed in the case of silica, where the vibrational lifetime of H-bonded OH dramatically shortens when the surface charge increases (high pH) 185 .…”
Section: Water Structuring and Orientationmentioning
confidence: 98%
“…This observation underlines the aforementioned asymmetry of water in response to positively and negatively charged surfaces. Interestingly, water dynamics in contact with zwitterionic lipids do not seem to be affected by the inversion of phosphate and choline (P-C versus C-P) in the headgroup 184 . The effect of the surface charge has also been observed in the case of silica, where the vibrational lifetime of H-bonded OH dramatically shortens when the surface charge increases (high pH) 185 .…”
Section: Water Structuring and Orientationmentioning
confidence: 98%
“…Characterization of ultrafast dynamics has been varied, yet common themes have emerged from these measurements. Perhaps the most consistent of these is that water dynamics are slower at lipid membrane interfaces than they are in bulk. This observation is not surprising, given that the membrane significantly disrupts the tetrahedral H-bond networks of water, but the extent of the disruption appears to be influenced by the headgroup structure and composition of the lipid membrane. The slowdown due to lipids has generally been interpreted as constrained motions of waters interacting with lipid headgroups; furthermore, the headgroup structure itself determines its extent.…”
Section: Model Systems and Case Studiesmentioning
confidence: 99%
“…Building on one-dimensional VSFG investigations of water orientations, , the dynamics of interfacial water have been measured with both time-resolved and two-dimensional heterodyne detected VSFG (TR-VSFG and 2D HD-VSFG, respectively), combining interface specificity and ultrafast time resolution. Tahara and co-workers found that the charge of a lipid or surfactant has a significant impact on the water dynamics as observed through spectral diffusion, which was significantly slower with anionic species compared to cationic. Backus and co-workers determined that the slowdown is independent of the water orientation . Interestingly, water dynamics at the zwitterionic lipid interface cannot be described as a combination of cationic and anionic interfaces, suggesting that dipole–dipole interactions, as well as H-bonding, drive interfacial dynamics .…”
Section: Model Systems and Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Evidence of enhanced hydrogen bonds (HBs) established between water molecules and the phospholipid heads has been described in experimental investigations from infrared spectroscopy 7,8 and sum frequency generation. 9,10 Nonetheless, far-infrared spectroscopy has shown that resonance mechanisms entangle the motion of phospholipid bilayers with their hydration water. 11 Such complex interactions between water molecules and hydrophobic heads cause perturbations in the dynamical properties of water.…”
mentioning
confidence: 99%